Head and neck cancers promote an inflammatory transcriptome through co-activation of classical and alternative NF-κB pathways - Yang, Xinping (Cancer Immunol Res, 2019)
Head and neck squamous cell carcinomas (HNSCC) promote inflammation in the tumor microenvironment through aberrant NF-κB activation, but the genomic alterations and pathway networks that modulate NF-κB signaling have not been fully dissected. Here, we analyzed genome and transcriptome alterations of 279 HNSCC specimens from The Cancer Genome Atlas (TCGA) cohort and identified 61 genes involved in NF-κB and inflammatory pathways. The top 30 altered genes were distributed across 96% of HNSCC samples, and their expression was often correlated with genomic copy number alterations (CNA). Ten of the amplified genes were associated with human papilloma virus (HPV) status. We sequenced 15 HPV(−) and 11 HPV(+) human HNSCC cell lines, and three oral mucosa keratinocyte lines, and supervised clustering revealed that 28/61 genes exhibit altered expression patterns concordant with HNSCC tissues, and distinct signatures related to their HPV status. RNAi screening using an NF-κB reporter line identified 16 genes that are induced by TNF-α or Lymphotoxin β (LTβ) and implicated in the classical and/or alternative NF-κB pathways. Knockdown of TNFR, LTΒR, or selected downstream signaling components established cross-talk between the classical and alternative NF-κB pathways. TNF-α and LTβ induced differential gene expression involving the NF-κB, IFN-γ and STAT pathways, inflammatory cytokines, and metastasis related genes. Improved survival was observed in HNSCC patients with elevated gene expression in T cell activation, immune checkpoints, and IFN-γ and STAT pathways. These gene signatures of NF-κB activation, which modulate inflammation and responses to the immune therapy, could serve as potential biomarkers in future clinical trials.